SISTEM SOSIAL, KULTURAL, DAN KEPRIBADIAN DALAM NOVEL EDENSOR KARYA ANDREA HIRATA (SOCIAL, CULTURAL, AND PERSONALITY SYSTEM IN THE EDENSOR NOVEL BY ANDREA HIRATA) - Gesit Aprianto (Universitas Lambung Mangkurat, 2022)
Social, Cultural, and Personality System in the “Edensor” Novel by Andrea Hirata. This study discusses the social, cultural, and personality systems found in the “Edensor” novel. This research is a qualitative research with a literary anthropological approach. The object of this research is a novel entitled